Akuntabilitas dan Transparansi Pelayanan Izin Mendirikan Bangunan Tahun 2020-2021 di Surakarta - Rizky Ardhian Nugraheni; Priyanto Susiloadi (Jurnal Mahasiswa Wacana Publik, 2022)
This research is contained about accountabilty and transparency of Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Surakarta City in the building permits service. This study is trying to find out how accountability and transparency in building permits service as a government responsipility to realize good governance. Accountability such an important thing to realize the good governance. Honesty and legal accountability, managerial accountability and policy accountability according to Ellwood are used in this study. To complete the accountability aspect, the theory of transparency is used according to Dwiyanto. This research uses a qualitative descriptive research type. The results of this study indicate that DPMPTSP Surakarta City has been accountable, seen from the fulfillment of 3 dimensions of accountability in the IMB, namely legal accountability and honesty, managerial accountability, and policy accountability. On legal accountability and honesty, officers related to IMB services use regulations that are used as guidelines, Perda Nomor 8 Tahun 2016 Tentang Bangunan Gedung. In managerial accountability, the Surakarta City DPMPTSP has made an effective and efficient IMB service flow. As well as on accountability policies, the Surakarta City DPMPTSP issued several policies that had a positive impact on various stakeholders, such as eliminating retribution fees for building houses of worship. On the criteria of transparency, information about services is easily accepted by the public. It can be said that the Surakarta City DPMPTSP has fulfilled the aspects of good governance.